A logic‐mathematical point of view of the truth: Reality, perception, and language. Issue 4 (6th March 2014) - Nescolarde‐Selva, Josué Antonio; Usó‐Doménech, Josep‐Lluis; Gash, Hugh
Abstract : In this article, the authors propose a theory of the truth value of propositions from a logic‐mathematical point of view. The work that the authors present is an attempt to address this question from an epistemological, linguistic, and logical‐mathematical point of view. What is it to exist and how do we define existence? The main objective of this work is an approach to the first of these questions. We leave a more thorough treatment of the problem of existence for future works. © 2014 Wiley Periodicals, Inc. Complexity 20: 58–67, 2015